Effective development of the speech of mentally retarded students on the basis of innovative technologies - Mamatkulova Lobar Tolibjonovna (Zien Journals, 2023)
this article covers methodological recommendations on the effective development of the speech of mentally retarded readers on the basis of innovative technologies.
Keywords: mentally retarded children; speech; separate education